2017
DOI: 10.1155/2017/7951793
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Angiotensin Converting Enzyme, Apelin, and New-Onset Atrial Fibrillation after Off-Pump Coronary Artery Bypass Grafting

Abstract: It has been shown that inflammation and oxidative stress are important factors in postoperative atrial fibrillation (POAF). Angiotensin converting enzyme (ACE) and apelin have a close relationship with inflammation and oxidative stress. The effect of ACE and apelin on POAF after off-pump coronary artery bypass grafting (OPCABG) remains a question. The concentrations of serum ACE, angiotensin II (Ang II), apelin, bradykinin (BK), malondialdehyde (MDA), and C reactive protein (CRP) were measured in the periopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
2
8
1
1
Order By: Relevance
“…We observed higher mean plasma BNP levels in the preoperative period, which might be associated with POAF, although other conditions may cause an elevation of plasma BNP. Xu and colleagues reported that increased LA size is related to POAF [11]. We found increased mean LA size among our study populations, and these findings have also been confirmed [7].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We observed higher mean plasma BNP levels in the preoperative period, which might be associated with POAF, although other conditions may cause an elevation of plasma BNP. Xu and colleagues reported that increased LA size is related to POAF [11]. We found increased mean LA size among our study populations, and these findings have also been confirmed [7].…”
Section: Discussionsupporting
confidence: 89%
“…Systemic arterial hypertension, decreased left ventricular function, chronic obstructive pulmonary disease (COPD), chronic renal failure, diabetes, and withdrawal of β-blockers are also responsible for POAF [1]. Smoking, LDL, statins, LA diameter, and left ventricular ejection fraction (LVEF) are significant risk factors for POAF preoperatively [11]. Preoperative HbA1c independently predicts the occurrence of AF after isolated OPCAB [12].…”
Section: Introductionmentioning
confidence: 99%
“…In ammation and ROS are still the main reason for the occurrence of POAF. 2,3,4,15 Recently, several studies have shown that intestinal bacterial microbiota dysbiosis was associated with different types of AF and duration of AF. 7,8 In this study, we demonstrated the characteristics of gut microbiota in patients underwent CABG are prone to developing POAF.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Some studies indicated in ammation, oxidative stress, and electrical remodeling are the main reasons for POAF. 3,4 However, the detailed mechanisms underlying POAF are largely unknown. Uncovering the driving factors and identifying strategies to impede POAF have attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…Rodrigo R, et al (2013) показали, что активность КАТ, СОД и ГПО в тканях предсердий была ниже у пациентов с ПОФП [13]. Кроме того, уровень плазменной концентрации МДА был выше в группе пациентов с ПОФП при проведении КШ на работающем сердце [14].…”
Section: Discussionunclassified